Understanding, comparing and learning from the four EPOCH early childhood obesity prevention interventions: A multi‐methods study. Issue 11 (15th June 2020) - Seidler, Anna Lene; Hunter, Kylie E.; Johnson, Brittany J.; Ekambareshwar, Mahalakshmi; Taki, Sarah; Mauch, Chelsea E.; Mihrshahi, Seema; Askie, Lisa; Campbell, Karen J.; Daniels, Lynne; Taylor, Rachael W.; Wen, Li M.; et al.
Summary: Background: Childhood obesity is a global problem. Early obesity prevention interventions are complex and differ in effectiveness. Novel frameworks, taxonomies and experience from the Early Prevention of Obesity in CHildren (EPOCH) trials were applied to unpack interventions. Objectives: Deconstruct interventions into their components (target behaviours, delivery features and behaviour change techniques [BCTs]). Identify lessons learned and future recommendations for intervention planning, delivery, evaluation and implementation. Methods: This multi‐methods study deconstructed the four EPOCH interventions into target behaviours, delivery features and BCTs from unpublished and published materials using systematic frameworks. Additionally, semi‐structured interviews were conducted with intervention facilitators and principal investigators. Results: Each trial targeted between 10 and 14 obesity‐related behaviours. Key variations in delivery features related to intensity, delivery mode and tailoring. BCTs consistently used across trials included goal‐setting, social support, shaping knowledge, role‐modelling and credible source. Recommendations from interview analyses include the importance of stakeholder collaboration and consideration of implementation throughout the study process. Conclusions: The combination of frameworks, methodologies and interviews used in this study is a major step towards understanding complex early obesity prevention interventions. Future work will link systematic intervention deconstruction with quantitative models to identify which intervention components are most effective and for whom.